Efektywność gospodarstw indywidualnych według skali produkcji i produktywności ziemi - Wysocki, Feliks; Gołaś, Zbigniew (Wydział Prawa i Administracji UAM, 1988)
The article contains the analysis of the efficiency of private farms according to the scale of production and the productivity of land. The research comprised farms specializing in cattle- and hog-breeding. The farms were divider into 4 classes with respect to the scale of final production brutto: to 250, 250-500, 500- - 1000, 1000 - 2000 thousand zloties per farm and within each class into 3 levels of land productivity: the value 0-50, 50-100, 100-200 thousand zloties of final production brutto per 1 ha of arable land. The research reveals that the productivity of farms grows together with the increase of scale; improved were in the first place the economic results, especially in farms with high level of land productivity. Satisfactory results with respect to efficiency and income achieved farms with the scale of production of 500 thousand zloties and more. In cases of high productivity of land it was possible already in farms with as little as 6 ha of arable land. However, since most of the farms were characterized by a medium level of land productivity, the area enabling to achieve satisfactory economic and financial efficiency should be equal to 10 ha of arable land. The results point out to the necessity of quickening the processes of concentration in private farming, first of all through rationalizing the land turnover, increasing the supplies of technical means of production to agriculture and through a more flexible policy of shaping sale prices of farm produce and means of production.
Effectivity of private farms according to the scale of production and productivity